Pengaruh Insentif Pajak Di Masa Pandemi Covid-19 Terhadap Kepatuhan Wajib Pajak Di Kabupaten Badung - Merta, I Ketut; Usadha, I Dewa Nyoman (Jurnal Metaverse ADPERTISI, 2023)
This research takes the object of the Badung Regency Revenue Agency with the variables Tax incentives and taxpayer compliance, the aim is to determine the effect of giving tax incentives during the Covid-19 pandemic on taxpayer compliance in Badung Regency. Qualitative research methodology with a questionnaire, population and sample of 100 respondents. Hypothesis: There is a level of influence from the variable giving tax incentives caused by the presence of Covid-19 on a taxpayer compliance. The results of the research on the tax incentive variable simultaneously have a "significant" effect on taxpayer compliance. The "positive and significant" tax incentive variable partially to the "Tax Incentive" taxpayer compliance variable has a "quite strong" correlation to "taxpayer compliance, and "taxpayer compliance" has a "strong enough" correlation to tax incentives. With the determination of tax incentives on taxpayer compliance in Badung Regency.